Analisis Tingkat Kesehatan Perbankan Dengan Pendekatan Risk Based Bank Rating (RBBR) Pada Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2018 - Putria D Sari; Abel Tasman (Universitas Negeri Padang, 2020)
The purpose of this research is to determine the level of health of the banks listed on the Indonesia Stock Exchange in 2014-2018 by using the risk-based bank rating approach. The type of research is quantitative descriptive. The technique of sample used is purposive sampling technique, the sample was obtained from consideration of certain criteria and obtained 4 BUMN Banks as samples, namely Bank Nasional Indonesia (BNI), Bank Rakyat Indonesia (BRI), Bank Tabungan Negara (BTN), and Bank Mandiri. Data was collected from the bank's financial statements that have been published by the bank in the Indonesia Stock Exchange during the period 2014-2018. The result showed that all banks have a healthy rating, especially Bank Nasional Indonesia (BNI) because it is able to manage risk well. Furthermore, Bank Rakyat Indonesia (BRI) and Bank Mandiri are classified as banks with healthy ratings. At the same time, the results of Bank Tabungan Negara (BTN) were also healthy, but from the liquidity aspect it was nearly high, so it is recommended to the bank to improve its liquidity risk management.Keywords: bank, health, risk-based bank rating.